Rapid Breakdown Time in Positive Impulse Voltages through Spectroscopy Analysis - Muhammad Ikhwanus; Takeshi Morimoto (Energies, 2024)
The air discharge phenomenon, characterized by its rapid and transient nature, is inherently unpredictable, emphasizing the need for a comprehensive understanding of its physical interactions. Our experimental setup involved voltage generators producing both positive and negative impulse voltages (±100 kV, ±125 kV, and ±150 kV) at a 3.5 cm gap distance in a needle-to-plane geometry. This setup facilitated the study of individual spectral lines of impulse voltage discharges, with a specific emphasis on examining oxygen transitions through spectroscopy analysis. To explore the influence of photon emission on the breakdown rate, we examined the correlation between decay time, excitation temperature, and peak intensity during the transition from an upper state to a lower state. Our findings reveal that positive impulse voltage discharges more rapidly than negative impulse voltages. This heightened discharge rate is attributed to the higher peak intensities of O II at 313.421 and 241.162 nm, as well as O IV at 337.806 nm, observed in the excited state, as opposed to O I at 777.417 nm in the combination state. The inference drawn from the larger peak intensity suggests that energetic photon emission plays a pivotal role in initiating and expediting electron discharge in positive voltages.